Determination of Age of Boys of Western Rajasthan by Epiphyseal Union of Bones at Ankle joint (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Characteristic changes during epiphyseal union helps provide an estimation of age. Currently there are no data on epiphyseal union for the purpose of age estimation specific to Western Rajasthan population. This study was conducted to formulate a data for age of epiphyseal union of bones at ankle. A total of Seventy five boys of age of 14 -20 were included. In the study the X ray films of the subjects were divided into three groups on the basis of degree of fusion. Firstly, those which were showing Non-union (N), secondly those showing partial union (P), and thirdly those showing complete union (C). Observations made were compared and discussed with the previous studies.
Keywords: Epiphyseal union; Ankle joint; distal end of tibia; distal end of fibula